Plant atlas 2020 : mapping changes in the distribution of the British and Irish flora - Stroh, P. A. (Peter A.); Walker, K. J.; Humphrey, T. A.; Pescott, O. L. (Oliver L.); Burkmar, R. J. (Richard J.) (Botanical Society of Britain and Ireland ; Princeton University Press, 2023)
An authoritative two-volume survey of the wild plants of Britain and IrelandPlant Atlas 2020 presents the results of field surveys by the Botanical Society of Britain and Ireland, building on past atlas surveys undertaken by the Botanical Society in the early and late twentieth century. Drawing on the work of thousands of botanists who covered the entirety of Britain and Ireland between 2000 and 2019, this two-volume book features introductory chapters that provide a detailed assessment of the changes to the region's flora over the past hundred years. Distribution maps and accompanying text and graphics display the phenology, altitudinal range, and time-series trends for some 2,700 native, alien, and hybrid species. With more than 30 million records gathered during the project, Plant Atlas 2020 will serve as an essential resource for the study and conservation of these wild plants and their vitally important habitats for decades to come.The most in-depth survey of British and Irish flora ever undertakenCovers some 2,700 species, including alien and hybrid plantsFeatures a wealth of distribution maps, each one accompanied by informative text and infographicsA must-have reference book for botanists, field naturalists, conservation organizations, government agencies, and anyone interested in the diverse plant life of the British IslesA monumental achievement decades in the makingPublished in association with the Botanical Society of Britain and Ireland.
Keywords: Phytogeography -- Great Britain.; Phytogeography -- Ireland.; Phytogéographie -- Grande-Bretagne.; Phytogéographie -- Irlande.; NATURE / Plants / Flowers.; Phytogeography; Great Britain; Ireland